Investigation of the properties of ZrC nanopowder synthesized by the carbothermal reduction method using phenolic resin - Farhad Farhang Rad; Mehri Mashhadi; Kianoosh Akbari Arateh (International Journal of Ceramic Engineering & Science, 2024)
Abstract Owing to economic reasons and the morphology of the surface of particles, carbothermal reduction is a suitable method for the synthesis of the desired materials. In this research, ZrC nanopowder was synthesized using phenolic resin as the carbon source and ZrO2 powder as the source of zinc by the carbothermal method. ZrO2 powder was milled for 1, 2, 3, 4, 6, and 7 h followed by combining with phenolic resin and ethanol with stoichiometric and nonstoichiometric ratios, and then the samples were pyrolyzed for 60 min at 800°C. Then, the samples were heat treated in an argon atmosphere in two stages at 1,600°C for 60 and 90 min. XRD and FE‐SEM were used to investigate the microstructure of the samples. By increasing the molar ratio and increasing the heat treatment time, the ZrC phase content in the samples increased so that the highest amount of ZrC phase was observed in the samples with the carbon to zirconium ratios of 1:6 and 1:9 and the holding time of 90 min. By increasing the heat treatment time, the average size of ZrC particles increased from 130 to 180 nm and the size of crystallites increased from 36 to 46 nm.